Analysis of Technology Acceptance Model (TAM) on The Use of Electronic Medical Records in Hospitals - Farah Shania; Vip Paramarta (CV. Publikasi Indonesia, 2024)
Hospitals have begun adopting Electronic Medical Record (EMR) systems to enhance healthcare services and meet service standards. The Technology Acceptance Model (TAM) has been widely utilized in research related to technology implementation in the healthcare sector, including electronic medical record systems. This research aims to analyze the acceptance of EMR systems in public hospitals (RSUD) using TAM, focusing on the main variables of perceived ease of use and perceived usefulness. A qualitative approach was employed, with data collected through literature review and in-depth interviews with medical staff at RSUD. The results indicate that perceived ease of use significantly influences the initial adoption of EMR, as medical personnel are more likely to embrace technology that they find easy to use. Additionally, perceived usefulness plays a crucial role in determining the sustained use of EMR, particularly when medical staff experience increased work efficiency and accuracy in managing patient data. This research also reveals that the implementation of EMR positively impacts patient satisfaction, enhancing service quality and the speed of information access. In conclusion, the factors of ease of use and usefulness are essential in ensuring the successful acceptance and sustainable use of EMR in public hospitals, as well as contributing to patient satisfaction.